1158 Ethnicity, demographics and growth parameters of children referred to east of england idiopathic Intracranial Hypertension (IIH) service. (17th August 2022) - Xu, Lucy; Whyte, Sharon; Muthusamy, Brinda; Harijan, Pooja; Krishnakumar, Deepa
Abstract : Aims: The primary aim of this study was to characterise the ethnicity, demographics and growth parameters of children referred to IIH clinic in the East of England. The secondary aim was to describe any association with IIH and obesity and to describe if there was an increased referral rate to the IIH clinic or IIH diagnoses during the COVID pandemic. Methods: A regional pathway of referral has existed within East of England for children with suspected IIH since 2014. A retrospective chart review between 2018 – 2021 was performed on an internal database of children referred to this IIH service. These patients typically presented with a combination of headache, optic disc oedema and high BMI. A total of 183 children were included in this study. These were split into pre-pandemic and post-pandemic cohorts between 2018-2019 and 2020-2021 respectively. From the hospital record system, demographic data including: age at time of referral, gender, local hospital trust and postcode, were collected. Growth parameters were recorded, which included height, weight and BMI. Presenting symptoms and final medical diagnoses were also obtained. The data was plotted to check its distribution and independent T tests were performed. In order to explore the distribution of referrals throughout the East of England, postcode heatmaps of referral data were done. Results: A total of 62 children (33.9%) received a diagnosis of IIH. 74 new children were referred to the IIH service in 2018-2019 and 83 during 2020-2021. 109 children had headache as presenting symptom, 83 had combination of headache and optic disc oedema whereas 55 had optic disc oedema without headache. The diagnosis rate of IIH remained remarkably stable with around 33% of patients referred to the clinic being diagnosed with IIH. The split between female and male patients was also particularly stable being consistently 66% female and 34% male. Children over 10 were more likely to be obese than pre-pubertal children under 10 ( figure 1 ). Post-pandemic, children were more likely to be overweight or obese than pre-pandemic ( figure 2 ). In children with a BMI over 30, around half went on to receive an IIH diagnosis. Bedfordshire hospitals trust had the highest overall referral rate in the East of England (32, 17.5%). East Suffolk and North Essex, and North West Anglia trusts had the second highest rates (21, 11.5%). A total of 148 children had their ethnicity recorded, the majority of patients were of White British ethnicity with a small percentage of ethnic minorities. Conclusion: Pre-pubertal children are more likely to present atypically with IIH, without raised BMI. The effect of the pandemic on high BMI in children compared to pre pandemic is similar to that reported in the adult population. The IIH diagnosis rate did not increase during the pandemic. There is a higher percentage of paediatric female IIH patients, which is consistent with findings in the adult population. A significant portion of children did not have their ethnicity (19.1%) or growth parameters (16.4%) recorded.